IC 9258 - Mine Power Systems (ecf7228c-74d1-4108-9a6b-ab4b1af27e27) - Lloyd A. Morley (The National Institute for Occupational Safety and Health (NIOSH), 2003)
This Bureau of Mines publication presents a comprehensive review of mine electrical power-system theory and practice. It discusses fundamental theory and the vital aspects to be considered in planning and designing mine electrical power systems. The report is divided into three major sections. The first presents the history of electricity in mining and the fundamentals of electrical phenomena and components. The second focuses on power-system components: motors, grounding systems, cables, and protective equipment and devices. The final section includes mine power-center equipment, switchhouses and substations, batteries, and mine maintenance.